Arte- diseño nuevos espacios de construcción simbólica, aplicando el arte mediante el diseño de interiores de la ciudad de Machala - Calle Sares, Evelyn Gissela (2016)
It has not been long since the supply and demand for interior design was strictly for a certain social class, where they hired designers to remodel and decorate their homes. This was not only used for homes, hotels and restaurants also they requested the services of designers. At present although the vast majority of people still think that interior design is for people who have high financial resources, these people are wrong and that little can redecorate homes, even with recyclable materials, only you need to fly use imagination and art.